Altered Expression of ADAMTSs and HAPLNs in Preeclamptic Placenta - Kandemir, Sevgi Irtegun; Taskin, Irmak Icen; Pektanc, Gulsum; Tekin, Mehmet Ali; Demircan, Kadir (Aves, 2018)
Objective: Preeclampsia (PE) is a pregnancy-specific complication defined by the new onset of hypertension and proteinuria during the second trimester of pregnancy. The pathogenesis of PE remains poorly understood. Revealing the key factors involved in placental dysfunction is critical for the understanding the pathogenesis of PE. The aim of this study was to determine the expression levels of ADAMTSs and their molecular partners, TIMP-3 and HAPLNs in the placental tissues of women with PE. Materials and Methods: Experimental research was conducted on control and preeclamptic placentas. A total of 10 control and 10 preeclamptic placentas were included in the present study. The expression levels of ADAMTSs, HAPLNs, and TIMP-3 were analyzed in two groups by Western blot. Results: The expression levels of ADAMTS-4, -8, -10, -12, -13, -14, -16, and -19 were considerably lower, whereas the expression levels of HAPLN-1, -2, and -4; ADAMTS-18; and TIMP-3 were significantly higher in preeclamptic placentas than in controls. Conclusion: Altered expression levels of ADAMTSs and their molecular partners, TIMP-3 and HAPLNs, may contribute to the pathogenesis of PE.
Keywords: ADAMTSs; TIMP-3; HAPLNs; preeclampsia; placenta